Teachers’ perceptions towards principals’ instructional supervisory role in selected secondary schools - Kinyua, Bessy Kageni; Obura, Elizabeth Atieno; Masinde, Johnson Mulongo (Institute of Advanced Engineering and Science, 2025)
Effective instructional supervision plays a crucial role in enhancing teaching quality and student learning. However, teachers’ perceptions towards supervision vary, some view it as supportive while others see it as fault-finding. This study examines teachers’ perceptions towards principals’ instructional supervisory practices to identify areas of improvement. The Administrative theory of supervision and a concurrent triangulation mixed approach guided the study. Purposive and simple random sampling were utilized to sample 127 teachers and 10 principals. A survey and an interview guide were employed to gather data which was analyzed using descriptive and inferential statistics. An independent sample t-test and one-way analysis of variance (ANOVA) were utilized to test the mean differences in teachers’ perceptions. Findings indicate that while most teachers recognize supervision as beneficial for professional development, a significant number perceive supervision as authoritarian. The results unveiled that teachers’ gender, age and education qualification did not significantly influence their perceptions [t(98)=1.468, p>0.05, F(4, 95)=0.556, and F(4, 95)=0.174, p>0.05]. The study concludes that fostering a positive supervisory environment can enhance teachers’ confidence, improve instructional strategies, and ultimately lead to better student outcomes.